The type-2 Streptococcus canis M protein SCM-2 binds fibrinogen and facilitates antiphagocytic properties - Lapschies, Antje-Maria; Aubry, Etienne; Kohler, Thomas P.; Goldmann, Oliver; Hammerschmidt, Sven; Nerlich, Andreas; Eichhorn, Inga; van Vorst, Kira; Fulde, Marcus (Frontiers in Microbiology, 2023)
Streptococcus canis is a zoonotic agent that causes severe invasive diseases in domestic animals and humans, but little is known about its pathogenesis and virulence mechanisms so far. SCM, the M-like protein expressed by S. canis, is considered one of the major virulence determinants. Here, we report on the two distinct groups of SCM. SCM-1 proteins were already described to interact with its ligands IgG and plasminogen as well as with itself and confer antiphagocytic capability of SCM-1 expressing bacterial isolates. In contrast, the function of SCM-2 type S. canis strains remained unclear to date. Using whole-genome sequencing and subsequent bioinformatics, FACS analysis, fluorescence microscopy and surface plasmon resonance spectrometry, we demonstrate that, although different in amino acid sequence, a selection of diverse SCM-2-type S. canis isolates, phylogenetically representing the full breadth of SCM-2 sequences, were able to bind fibrinogen. Using targeted mutagenesis of an SCM-2 isolate, we further demonstrated that this strain was significantly less able to survive in canine blood. With respect to similar studies showing a correlation between fibrinogen binding and survival in whole blood, we hypothesize that SCM-2 has an important contribution to the pathogenesis of S. canis in the host.